2018
DOI: 10.1038/s41598-018-28804-0
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal optical imaging revealed different spatiotemporal patterns of facial cardiovascular activities

Abstract: Human cardiovascular activities are important indicators of a variety of physiological and psychological activities in human neuroscience research. The present proof-of-concept study aimed to reveal the spatiotemporal patterns of cardiovascular activities from the dynamic changes in hemoglobin concentrations in the face. We first recorded the dynamics of facial transdermal blood flow using a digital video camera and the Electrocardiography (ECG) signals using an ECG system simultaneously. Then we decomposed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…These areas contain significant PPG signal-to-noise ratios. The maps are somewhat similar to those presented in [82].…”
Section: Image Sequencesupporting
confidence: 81%
“…These areas contain significant PPG signal-to-noise ratios. The maps are somewhat similar to those presented in [82].…”
Section: Image Sequencesupporting
confidence: 81%
“…al. 27 , in which unique facial spatiotemporal patterns were observed, occasionally asymmetric, related to cardiovascular activity, and assumed to be related to the ANS activity, hence the relation to the emotional state.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al suggested that cardiovascular activities presented different dynamic properties within different facial sub-regions; moreover, blood vessels in the nasal region pass through a small space between the nasal bone and the skin. Furthermore, the nasal region has a higher concentration of blood vessels than other parts of the face [ 25 ].…”
Section: Discussionmentioning
confidence: 99%